2010
DOI: 10.1017/s0047279410000929
|View full text |Cite
|
Sign up to set email alerts
|

Refugees, Acculturation Strategies, Stress and Integration

Abstract: The advent of super-diversity and politicisation of migration has been accompanied by heightened interest in migrant settlement. Much has been written in policy and academic fields about the importance of integration particularly in relation to the settlement of refugees. However little attention has been paid to the varied settlement experiences of individual refugees or how personal, cultural and experiential factors combine to influence settlement experiences. This paper turns to cross-cultural psychology's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 31 publications
3
140
0
3
Order By: Relevance
“…This result replicates quantitatively what Phillimore (2011) showed through a qualitative analysis of interviews with refugees and demonstrates, as Yijälä and Jasinskaja-Lahti (2010) highlighted with potential Russian migrants, that early-stage acculturation preferences of Syrian and Iraqi asylum seekers recently arrived in Europe are influenced by these perceptions. Even before their arrival in the host country, asylum seekers, and more generally migrants, are often deeply embedded in social networks with people living in their destination country (Massey, 1990;Portes & Sensenbrenner, 1993).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This result replicates quantitatively what Phillimore (2011) showed through a qualitative analysis of interviews with refugees and demonstrates, as Yijälä and Jasinskaja-Lahti (2010) highlighted with potential Russian migrants, that early-stage acculturation preferences of Syrian and Iraqi asylum seekers recently arrived in Europe are influenced by these perceptions. Even before their arrival in the host country, asylum seekers, and more generally migrants, are often deeply embedded in social networks with people living in their destination country (Massey, 1990;Portes & Sensenbrenner, 1993).…”
Section: Discussionsupporting
confidence: 80%
“…This idea was supported by several empirical studies (Jasinskaja-Lahti, Liebkind, Horenczyk & Schmitz, 2003;Phillimore, 2011;Zagefka, Gonzales & Brown, 2011). For example, Phillimore (2011) showed, through interviews with refugees from various countries, that perceptions of majority members' attitudes toward them affected their desire to participate in the host society. This author argued that the negative headlines in the media vilifying asylum seekers and reporting their criminal behaviours reduce their confidence and lead them to endorse either separation or marginalization strategies.…”
Section: Perception Of National Majority Members' Expectationsmentioning
confidence: 87%
“…The attractiveness of the concept is continuously increasing, so too is the complexity and diversity of the cultural and social fabric of Western societies. As such, some authors have identified this process as being 'super-diverse' [1,2] or 'hyperdiverse' [3] to overcome the limitations of the complex conceptualisations of today's increasingly diverse societies inherent in previous accounts. Therefore, larger cities in the UK, such as Birmingham-and elsewhere-have been described as 'super-diverse'.…”
Section: Introductionmentioning
confidence: 99%
“…In order to integrate and acculturate refugees in their host countries it is necessary to raise the importance of a more balanced discussion of migration from where asylum seekers and refugees are vilified by the state, media, and general population to a point where the reality of the refugee experience is understood, and they are treated with more sympathy and less fear, and provided with appropriate support to settle (Phillimore 2011).…”
Section: The Rejection Of Refugees and Migrants By The Mediamentioning
confidence: 99%